Pengaruh pupuk kasgot terhadap pertumbuhan dan hasil tanaman sawi hijau (Brassica juncea L.) - Fizykri Alhamda; Setyono Setyono; Nani Yulianti (JURNAL AGRONIDA, 2025)
Mustard greens are in great demand by the community because they have an important role in meeting food and nutritional needs. This study aims to determine the effect of kasgot fertilizer (maggot excrement residue) on the growth and yield of mustard greens (Brassica juncea L.). This study used Complete Random Design (RAL) with single factor consisting of 6 treatment levels, namely 0 g/plant without fertilizer, 125 g/plant of kasgot fertilizer, 150 g/plant of kasgot fertilizer,175 g/plant of kasgot fertilizer, 200 g/plant of kasgot fertilizer, and 4.5 g/plant of NPK fertilizer. The recommended dose of kasgot fertilizer used is 150 g/plant kasgot fertilizer. The results of the research showed that application of kasgot fertilizer and NPK fertilizer to mustard greens give the same results, so that kasgot fertilizer can be an alternative to the use of NPK fertilizer. Applying all doses of kasgot fertilizer is able to increase plant height, number of leaves, crown diameter, leaf area, crown fresh weight, root fresh weight, total plant fresh weight, crown dry weight, root dry weight, and total dry plant weight.